Time-of-flight methodologies with large-area diamond detectors for the effectively characterization of tens MeV protons. (1st April 2022) - Salvadori, M.; Andreoli, P.L.; Cipriani, M.; Cristofari, G.; De Angelis, R.; Malko, S.; Volpe, L.; Perez Hernandez, J.A.; Apiñaniz, J.I.; Morace, A.; Antici, P.; Migliorati, M.; et al.
Abstract: A novel detector based on a polycrystalline diamond sensor is here employed in an advanced time-of-flight scheme for the characterization of energetic ions accelerated during laser-matter interactions. The optimization of the detector and of the advanced TOF methodology allow to obtain signals characterized by high signal-to-noise ratio and high dynamic range even in the most challenging experimental environments, where the interaction of high-intensity laser pulses with matter leads to effective ion acceleration, but also to the generation of strong Electromagnetic Pulses (EMPs) with intensities up to the MV/m order. These are known to be a serious threat for the fielded diagnostic systems. In this paper we report on the measurement performed with the PW-class laser system Vega 3 at CLPU (∼30 J energy, ∼10 21 W/cm 2 intensity, ∼30 fs pulses) irradiating solid targets, where both tens of MeV ions and intense EMP fields were generated. The data were analyzed to retrieve a calibrated proton spectrum and in particular we focus on the analysis of the most energetic portion ( E > 5.8 MeV) of the spectrum showing a procedure to deal with the intrinsic lower sensitivity of the detector in the mentioned spectral-range.